"Not All Environmentalists Are Like That … ": Unpacking the Negative and Positive Beliefs and Perceptions of Environmentalists. Issue 7 (3rd October 2019) - Klas, Anna; Zinkiewicz, Lucy; Zhou, Jin; Clarke, Edward J. R.
ABSTRACT: Limited research to date has qualitatively explored the perceptions members of the public who are not environmental activists hold of environmentalists. Therefore a qualitative survey was conducted with 89 US residents aged 21–53 ( M age  = 32.74, SD age  = 7.89) to obtain an in-depth understanding of how non-activists within the public perceive environmentalists. Data obtained were analyzed using thematic analysis and demonstrated that non-activist perceptions of environmentalists contained both positive and negative components. Environmentalists were seen to value nature and to be actively involved in bringing about positive environmental change (positive component), yet were also viewed as aggressive in their behaviors and stubborn in their beliefs (negative component). Further still, it was found that environmentalists were more likely to be perceived positively when they engaged in individual-level, private sphere behaviors (such as recycling), and negatively when they engaged in collective-level, public sphere behaviors (such as protesting). These findings not only challenge the assumption that members of the public typically evaluate environmentalists negatively, they also outline why some individuals may fail to identify as an environmentalist and engage in pro-environmental behavior. Furthermore, they also provide some insight as to why some environmentalists find it difficult to advocate for system change that results from collective action within the public sphere.